Respuesta :

Answer:

[tex]d = \sqrt{13}[/tex]

Step-by-step explanation:

Use the Distance Formula to help you determine the distance between the two following points:

-Distance Formula:

[tex]d = \sqrt{(x_{2} - x_{1})^2 + ( y_{2} - y_{1})^2}[/tex]

(where [tex](x_{1}, y_{1})[/tex] represents the first point and [tex](x_{2}, y_{2})[/tex] represents the second point)

-Apply the two following points onto that equation:

[tex]d = \sqrt{(7 - 5)^2 + (6 - 3)^2}[/tex]

[tex](x_{1}, y_{1}) = (5, 3)[/tex]

[tex](x_{2}, y_{2}) = (7, 6)[/tex]

-Solve the equation:

[tex]d = \sqrt{(7 - 5)^2 + (6 - 3)^2}[/tex]

[tex]d = \sqrt{2^2 + 3^2}[/tex]

[tex]d = \sqrt{4 + 9}[/tex]

[tex]d = \sqrt{13}[/tex]

So therefore, the distance is [tex]\sqrt{13}[/tex].